Innovative Entrepreneurship in Education: A New Look in the Students Training Content and Existing Problems - Safin, Rais S.; Shaidullina, Albina R.; Alikhanova, Rovzat A.; Muskhanova, Isita V.; Yusupkhadzhieva, Tatyana V.; Dzhamalkhanova, Lolita A.; Mezhidova, Fariza V.; Nigmetzyanova, Venera M.; Akhmetov, Linar G. (International Review of Management and Marketing, 2016)
This article is aimed at scientific and methodological justification of students' training content to innovative entrepreneurship. The leading method in the study of this problem is the analysis of students' innovative entrepreneurship learning experience in Russian universities, which reveals the predominance of the traditional approach in the content of students' training, as well as unwillingness of the teaching staff and students to innovate. The article identified the necessary competences in the field of innovative entrepreneurship (professional, business, functional, social and communicative), as well as entrepreneurial qualities (integrity, credibility, intelligence, presence of imagination, ability to make decision, ability to organize control, to provide justification of decisions); the methodology of students' gradual of entrepreneurial competences is developed; factors blocking the effectiveness of the students' entrepreneurial competences' formation are revealed. Keywords: Innovative-Entrepreneurial Competences, Students, Content of Training, Methodology. JEL Classifications: A12, H11, I21, I28